Anesthesia for separation of conjoined twin a case report - Amin, Md Nurul; Miah, Md Akkas; Rahman, Md shamsur; Akhter, Naira (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Pygopagus is a rare type of conjoined twins and the incidence is about 6% and these babies are united dorsolaterally in the sacrum and the perineum. Conjoined twins were being separated with increasing frequency and success, concomitant with the improvements being made in the care of pediatrics surgical and anesthesiologist team. The conjoined twins which were presented to us for anesthesia were female pygopagus. They were born on March 21, 2010 in remote village of Sylhet, at home by an uncomplicated vaginal delivery. At birth, the twins were 2.8 kg attached at their back. They baby was separate organ system except a common anus. The operation was to be performed on the lower intestinal tract and on the nervous system at the same time it was decided to include a neurosurgeon in this team. At the age of 100 days when both weight 5.4 kg general condition was good, two team of surgeon and anesthetist, at beginning one operation table two anaesthesia machine with individual monitoring device required preponed. Since surgery was uneventfully. Despite this decision or perhaps even because of it, there was no infection postoperatively. The twins recuperated well from their adventure. DOI: http://dx.doi.org/10.3329/jbsa.v24i1.19798 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(1): 34-37